Rodent Models for Investigating the Dysregulation of Immune Responses in Type 1 Diabetes - Feng-Cheng Chou; Heng-Yi Chen; Shyi-Jou Chen; Mei-Cho Fang; Huey-Kang Sytwu (Journal of Diabetes Research)
Type 1 diabetes (T1D) is an autoimmune disease mediated by T cells that selectively destroy the insulin-producing β cells. Previous reports based on epidemiological and animal studies have demonstrated that both genetic factors and environmental parameters can either promote or attenuate the progression of autoimmunity. In recent decades, several inbred rodent strains that spontaneously develop diabetes have been applied to the investigation of the pathogenesis of T1D. Because the genetic manipulation of mice is well developed (transgenic, knockout, and conditional knockout/transgenic), most studies are performed using the nonobese diabetic (NOD) mouse model. This paper will focus on the use of genetically manipulated NOD mice to explore the pathogenesis of T1D and to develop potential therapeutic approaches.